2013
DOI: 10.1093/geront/gnt069
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Trauma and Stress, Coping Resources, and Mental Well-Being Among Older Adults in Prison: Empirical Evidence Linking Theory and Practice

Abstract: As prisons are forced to deal with an aging population, research in this area can take the preliminary steps to enhance understanding of risk and resilience among older adults in prison. This understanding will aid in the development and improvement of integrated theory-based interventions seeking to increase human rights, health, and well-being among older adults in prison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Further studies were excluded from analyses because they did not report on the interaction effects for trauma experience and religiosity. Significant interaction effects were found in Maschi et al (, mediation between continuous lifetime trauma exposure and mental disorders symptoms) and Stratta et al (). Partial effects were found in Wortmann et al (), Staton‐Tindall et al (), and Park et al ().…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Further studies were excluded from analyses because they did not report on the interaction effects for trauma experience and religiosity. Significant interaction effects were found in Maschi et al (, mediation between continuous lifetime trauma exposure and mental disorders symptoms) and Stratta et al (). Partial effects were found in Wortmann et al (), Staton‐Tindall et al (), and Park et al ().…”
Section: Resultsmentioning
confidence: 86%
“…Some of the studies focusing on general religious coping (without differentiating between positive and negative coping) showed positive associations between this variable and good psychological functioning: Currier et al ()—positive association with PTG and negative with distress; Hawthorne, Youngblut, and Brooten ()—negative associations with grief, depression, PTSD (only in women), and positive with PTG (only in women); Maschi, Viola, and Morgen ()—positive link with global mental health; Saxon et al (), and negative links with mental disorders (only in women). Nevertheless, no significant links with symptoms of PTSD were demonstrated in a longitudinal study (Bryant‐Davis et al, ; all participants were women); prayer as coping was not linked with symptoms of depression in Ai et al ().…”
Section: Resultsmentioning
confidence: 99%
“…For instance, one study conducted in a state prison found that nearly 80% of older prisoners had experienced at least one or more traumatic or stressful events during their lifetime (Haugebrook, Zgoba, Maschi, Morgen, & Brown, 2010). A more recent study found similar rates of stress and trauma in 677 older prisoners, with 70% experiencing one or more traumatic or stressful life events and an average of 11 occurrences over their lifetime (Maschi, Viola, & Morgen, 2014). This included episodes of major distress over the past year, with more than half of participants reporting abuse or stress while incarcerated, money problems, and high levels of subjective distress (Maschi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study found similar rates of stress and trauma in 677 older prisoners, with 70% experiencing one or more traumatic or stressful life events and an average of 11 occurrences over their lifetime (Maschi, Viola, & Morgen, 2014). This included episodes of major distress over the past year, with more than half of participants reporting abuse or stress while incarcerated, money problems, and high levels of subjective distress (Maschi et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Living in a closed environment like a prison can change people, causing depersonalization and destructuration of the self. Prisoners lose the property of material objects, the ability of self-determination, their privacy, and also sexual identity can be challenged 8 . Depression and suicide are two of the main problems that might occur because of freedom restriction.…”
Section: Introductionmentioning
confidence: 99%